Comparison of the efficacy of cognitive rehabilitation and neurofeedback on specific learning disorder among primary school children of Tehran, Iran. - Naimian, Nazgul; Hajebi, Majid Zargham; Nokani, Mostafa (Journal of Basic Research in Medical Sciences, 2022)
Introduction: Specific learning disorder is an impairment in general academic skill that is identified in reading, mathematics and written expression fields; besides, it creates a major problem in academic achievement, job performance or daily life activities. The present study was aimed to compare the efficacy of cognitive rehabilitation with neurofeedback on specific learning disorder (math, reading and spelling) in primary school children in District 5 of Tehran. Materials and Methods: The methodology of this research was quasi-experimental with pre-testpost-test design with control group. Using the Learning Disability Evaluation Scale, 45 patients in three groups were selected as experimental group (15 patients for cognitive rehabilitation and 15 patients for neurofeedback) and control group (15 patients). Then, the interventions were provided to the experimental group and the control group used the usual school training. Pre-test and post-test were taken from both experimental and control groups, after the intervention on the experimental group, the pre-test and post-test results of all three groups were compared with each other. The Learning Disability Evaluation Scale (LDES-R2), developed by McCarney, was used in the study. Multivariate analysis of covariance, with SPSS 22 software was used for data analysis. Results: The results of the study showed that after the intervention, the treatment group was improved in the specific learning variables of reading, writing and math (P < 0.001). And the effect of cognitive rehabilitation approach was greater than the efficacy of neurofeedback (P < 0.001). Conclusion: By improving specific learning disorders in children, their problems might be reduced and the effect of treatment might be improved. Though, in case of specific learning disorders in the children, we would need much more thorough treatments.